Proteomic Analysis of Pesisir Bull Sperm in Different Age Groups for the Identification of Reproductive Function Proteins - Anwar, P.; Maulana, T.; Sumantri, C.; Arifiantini, I.; Gunawan, A. (Tropical Animal Science Journal, 2025)
Pesisir cattle are native to Indonesia and originate from West Sumatra. It is known for its high environmental adaptability and can be further developed using a proteomic approach. The proteomic approach for testing the fertility of Pesisir bulls is an important factor in determining a potentially superior breed. Proteomic studies of reproduction in Pesisir bulls have not been widely conducted. This study aimed to identify and characterize functional sperm proteins in Pesisir bulls that are associated with reproductive processes. Semen samples were collected from 12 pesisir bulls aged 2–4 years and grouped into three age categories. Protein profile analysis was performed using polyacrylamide gel electrophoresis with 1D-SDS-PAGE, followed by proteolytic digestion of the proteins in the gel and protein identification using LC-MS/MS analysis. Protein functions were predicted based on analysis of biological annotations generated using UniProt, Venny, PANTHER, and STRING. Based on the evaluation of fresh semen, sperm motility in Pesisir bulls was found to increase with age. Proteomic analysis successfully identified 334 proteins in the sperm of Pesisir bulls. Among these, two proteins, ZPBP and SPACA3, were identified as involved in reproductive and fertilisation processes. Functionally, both proteins play crucial roles in acrosomal events during fertilisation. Gene Ontology analysis showed that most proteins in sperm are involved in various biological processes, including cellular activities, metabolic processes, and molecular functions related to catalytic activities. In conclusion, SPACA3 and ZPBP proteins were identified as potentially involved in reproductive processes and may serve as fertility markers in Pesisir bulls.